The Influence of Organizational Culture and Work Motivation on Employee Performance through Employee Organizational Citizenship Behavior at Hotel Sahid Montana in Malang City - Gilang Rasmardi Astry; Mokh. Natsir; Tanto Gatot Sumarsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze the effect of organizational culture and work motivation on OCB and the performance of Sahid Montana hotel employees and to analyze the influence of organizational culture and work motivation on employee performance if mediated by OCB. The population of this study is the population of this study are the employees of the first and second Sahid Montana hotels, totaling 105 employees with a total sample of 83 employees. The data analysis technique used is path analysis (Path Analysis). The results of the study show that the better the organizational culture and the higher the employee's work motivation, the better organizational citizenship behavior will be. The better the organizational culture and the higher the employee motivation will improve employee performance. Organizational culture and work motivation affect employee performance through OCB. To be able to improve the performance of Sahid Montana hotel employees, leaders need to create a good organizational culture by keeping abreast of science and technology developments and paying attention to employees to achieve satisfaction. Employees are motivated through opportunities to innovate work and leaders can provide suggestions and constructive criticism. In addition, employees are given an understanding to have the attitude of being able to refrain from complaining and have the willingness to tolerate without complaining.